Role of Microcredit on the Education: A Study on NGOs in Bangladesh - Roy, Ishita; Biswas, Pronab (Asian Business Review, 2016)
Bangladesh is a pioneer of the conceptualizing micro-credit program. It has undertaken some such programs to reduce poverty and bring about socio-economic changes in the rural community. Among them, microcredit plays vital role in promoting education. So micro-credit is considered as vital tools to promote the education and reduce drop out. Presently Microfinance popularly known as micro-credit. Now there are many types of microcredit organizations, we can see throughout the country. The common micro-credit institutions are GB, BRAC, ASA. This study explores the role of micro credits on the education, who had acquired micro credits from different microcredit organizations. Primary research was carried out with the help of a major NGO’s who give loan for education. Two hundred in-depth personal interviews were conducted by the author Roy, I. and Biswas, P. from February to August 2015. Most of the developing countries like Bangladesh; people are poor especially in the rural areas people who are unable to send their children to school. Though Bangladesh Government provides some reading and writing materials to all level of students throughout the Bangladeshi students. But it is not sufficient, and it can’t motivate parents to send their children school. Because of the high cost of education parents are discouraged to educate their children. In such a situation some major microcredit institutions provide money for their children education who is the member of these institutions. They sometimes provide money without any condition or sometimes conditionally. Such major micro-credit organizations are GB, BRAC, and ASA.
Keywords: Grameen Bank; BRAC; ASA; Micro-Credit; Education; Frequency; Zero-order correlation